IMPLEMENTATION OF GUIDED INQUIRY LEARNING MODELS TO TRAIN STUDENTS CRITICAL THINKING SKILLS IN SUB MATERIAL GASES STATE EQUATION - FITRI YUNITA, AULIA; ARIFIN IMAM SUPARDI, ZAINUL (Inovasi Pendidikan Fisika, 2018)
In the 21st century students are required to have learning skills and innovation. One of the learning skills is critical thinking skills (CTS). Guided Inquiry is one of the learning model that able to develop CTS students through its learning syntax. This study aims to describe the quality of learning implementation and improvement of CTS. The enhanced CTS includes indicators of interpretation, analysis, evaluation, inference, and explanation. The research design is pre-experimental with one-group pretest-posttest design. The subjects of the study are students of class XI MIA 8 and XI MIA 7 SMA Muhammadiyah 2 Surabaya. The improvement of CTS was analyzed using paired t-test and normalized gain-score analysis. The results showed that the guided inquiry implementation is 100% with good criteria and CTS improved significantly with gain score categorized as medium. Keywords: guided inquiry, critical thinking skills, gases state equation